Expert Opinion Analysis on Renewable Hydrogen Storage Systems Potential in Europe - Davide Astiaso Garcia; Federica Barbanera; Fabrizio Cumo; Umberto Di Matteo; Benedetto Nastasi (Energies, 2016)
Among the several typologies of storage technologies, mainly on different physical principles (mechanical, electrical and chemical), hydrogen produced by power to gas (P2G) from renewable energy sources complies with chemical storage principle and is based on the conversion of electrical energy into chemical energy by means of the electrolysis of water which does not produce any toxic or climate-relevant emission. This paper aims to pinpoint the potential uses of renewable hydrogen storage systems in Europe, analysing current and potential locations, regulatory framework, governments’ outlooks, economic issues, and available renewable energy amounts. The expert opinion survey, already used in many research articles on different topics including energy, has been selected as an effective method to produce realistic results. The obtained results highlight strategies and actions to optimize the storage of hydrogen produced by renewables to face varying electricity demand and generation-driven fluctuations reducing the negative effects of the increasing share of renewables in the energy mix of European Countries.